Airport development and sustainability: a case of multi-airport system in Italy. (1st January 2014) - Fasone, Vincenzo; Maggiore, Pasquale
During the last decades, airports have been substantially transformed in a dynamic and competitive industry. Today each airport faces the challenging task of coordinating all the services provided to work efficiently. Airports need to find a way to overcome economic, financial and infrastructural problems in a coherent attempt of definition of a conceptual framework of the airport business as a whole. In this context, an increasing relevance has the model of multi-airport system (MAS) able to overcome economic and financial issues and to provide a sustainable infrastructure management strategy. The role played by management and technicians has been studied in order to define a recognisable (well-known) model for airport sustainability. The research uses case study analysis approach to obtain experimental outlines by Italian air transport context as representative case of MAS approach. More in details, business and technical data accounted from Puglia's airports have been considered. The main findings of the research seems to demonstrate that the basic hypothesis, according to which a well-structured multi-airport system can contribute significantly to infrastructure management and development in a way of sustainability, is valid only if it is supported by a coordinated managerial approach.